2018
DOI: 10.1038/s41598-018-23637-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Differences in cognitive functions between cytomegalovirus-infected and cytomegalovirus-free university students: a case control study

Abstract: Cytomegalovirus (CMV) is the herpetic virus, which infects 45–100% people worldwide. Many reports suggest that CMV could impair cognitive functions of infected subjects. Here we searched for indices of effects of CMV on infected subjects’ intelligence and knowledge. The Intelligence Structure Test I-S-T 2000 R was used to compare IQ of 148 CMV-infected and 135 CMV-free university students. Infected students expressed higher intelligence. Paradoxically, their IQ decreased with decreasing concentration of anti-C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Based on the theoretical grounding described above and our experience with the research of two unrelated species of parasites, Toxoplasma gondii (Flegr et al, 2005(Flegr et al, , 2000 and human cytomegalovirus (Chvatalova et al, 2018), we strongly recommend the usage of permutation tests for contaminated data at https://github.com/ costlysignalling/Permutation_test_for_contaminated_data whenever any properties of parasite-infected and parasite-free individuals are compared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the theoretical grounding described above and our experience with the research of two unrelated species of parasites, Toxoplasma gondii (Flegr et al, 2005(Flegr et al, , 2000 and human cytomegalovirus (Chvatalova et al, 2018), we strongly recommend the usage of permutation tests for contaminated data at https://github.com/ costlysignalling/Permutation_test_for_contaminated_data whenever any properties of parasite-infected and parasite-free individuals are compared.…”
Section: Discussionmentioning
confidence: 99%
“…A Monte Carlo simulation was performed with R 3.3.3. We generated a population of 150 parasite-free and 150 infected subjects (mean intelligence was 101.5 in the parasite-free group and 98.5 in the infected groupthe between-group difference was 3, the population mean intelligence was 100) (Flegr et al, 2013(Flegr et al, , 2003Chvatalova et al, 2018). Subjects were normally distributed around group means with equal standard deviations (SD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of CMV infection on intelligence and cognitive performance, particularly in young and middle-aged individuals, have not been extensively studied. An earlier study [60], which stemmed from the first author's diploma thesis [61], reported negative impacts of CMV infection on the IQ of university students. However, this study was retracted due to an error in the permutation tests, specifically the mislabeling of infected and uninfected individuals' codes [62].…”
Section: Intelligence and CMV Infectionmentioning
confidence: 99%